Bioplastic Synthesis based on Modified Heat Moisture Treatment (HMT) Sago Starch (Metroxylon Sp) and its Application as Powdered Coffee Packaging - Emanratu, John Dewan; Santoso, Budi; Angela Myrra Puspita Dewi (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
The physical, mechanical and degradability properties of bioplastics made from natural and Heat Moisture Treatment (HMT) modified sago starch and their application as packaging for ground coffee were studied. HMT modification increased the amylose content by 4% and decreased the expandability by 7.16%. HMT-modified starch can also reduce the hydrophilicity of bioplastics as indicated by a decrease in WVTR value by 10% and solubility by 59%. The results also showed that bioplastic from natural and HMT-modified sago starch can be degraded on day 9 by 16% and 34%, respectively. Bioplastic from HMT-modified sago starch can be applied as a packaging for ground coffee with the speed of dissolving in hot water for 116 seconds. Keywords: sago starch, Heat Moisture Treatment, ground coffee